Exploring the Career Pipeline: Gender Differences in Pre-Career Expectations - Schweitzer, Linda; Ng, Eddy; Lyons, Sean; Kuron, Lisa (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2011)
The pipeline theory suggests that increasing the number of women in male-dominated fields should lead to more equality in the labour market. This perspective does not account for differences in the expectations of men and women within the pipeline, which may serve to perpetuate inequities. This study explores the differences in the choice of academic preparation, career expectations, and career priorities of 23,413 pre-career men and women using a large sample of Canadian post-secondary students who are about to embark on their first careers. Our results indicate that, although women are increasingly entering male-dominated fields such as science/engineering and business, they continue to have lower salary expectations and expect a longer time to promotion than their male counterparts. That said, young women in male-dominated fields reported higher salary expectations than those in female-dominated fields. Additionally, young women indicated a preference for beta career priorities (e.g., work/life balance) that are associated with lower salaries, while men indicate a preference for alpha career priorities (e.g., build a sound financial base) that are associated with higher salaries. Our study also found that although women are entering the pipeline for male-dominated fields in greater numbers, it does not necessarily result in more equality for women in the labour market. We conclude that the inequities in the labour market are evident within the pre-career pipeline in the form of gendered expectations. We recommend a number of interventions that might address the expectation gap and therefore improve gender equity in the labour market.